The Role of Teachers in Developing Nationalist Attitudes in Class V Elementary School Students - Herawiyana, Herawiyana; Maskanah, Hesti (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2018)
This research aims to describe the role of teachers in developing nationalistic attitudes in fifth grade elementary school students. This research was conducted at SDN NO. 34/1 Teratai, Muara Bulian. This research was aimed at determining teachers' skills in developing nationalist attitudes in elementary school students. This research uses a qualitative research approach, with a phenomenological research method. The subjects of this research were teachers and students of class V C. Data collection techniques in this research used observation and interviews. Data analysis uses data reduction steps, data presentation, and drawing conclusions. Checking the validity of the data uses triangulation techniques. The research results show that the role of teachers in developing nationalist attitudes in fifth grade elementary school students focuses on the role of teachers in developing nationalist attitudes through 1) teachers as educators in developing nationalist attitudes, (2) teachers as facilitators in developing nationalist attitudes; (3) teachers as models and role models in developing nationalist attitudes; (4) teachers as motivators in developing nationalist attitudes; (5) teachers as guides in developing nationalist attitudes; (6) forms of manifestation of students' nationalist attitudes, such as attitudes of unity and oneness, love of the homeland, willingness to sacrifice, tolerance, pride as an Indonesian nation and homeland, and discipline.